2022
DOI: 10.3390/toxins14010056
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Synthesis and Stability Assessment of Aflatoxin B1-Lysine and Aflatoxin G1-Lysine

Abstract: Aflatoxins B1 (AFB1) and G1 (AFG1) are carcinogenic mycotoxins that contaminate crops such as maize and groundnuts worldwide. The broadly accepted method to assess chronic human aflatoxin exposure is by quantifying the amount of aflatoxin adducted to human serum albumin. This has been reported using ELISA, HPLC, or LC-MS/MS to measure the amount of AFB1-lysine released after proteolysis of serum albumin. LC-MS/MS is the most accurate method but requires both isotopically labelled and unlabelled AFB1-lysine sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…AFB 1 -epoxide undergoes rapid hydrolysis in an aqueous environment to form the AFB 1 -dihydrodiol, which is in equilibrium with AFB 1 -dialdehyde [ 12 ]. The initial AFB 1 solution in dichloromethane (DCM) was clear, however following the addition of DMDO, drying and reconstitution in 0.1 M sodium bicarbonate (pH 8.1), the solution was an intense yellow colour, in line with previous observations that indicated the presence of the dialdehyde [ 19 ]. To maximize the amount of AFB 1 adducts on the reference material (RM) serum, while ensuring that the adducts formed were similar to those formed in vivo it was necessary to determine the theoretical maximum molar ratio of AFB 1 to HSA.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…AFB 1 -epoxide undergoes rapid hydrolysis in an aqueous environment to form the AFB 1 -dihydrodiol, which is in equilibrium with AFB 1 -dialdehyde [ 12 ]. The initial AFB 1 solution in dichloromethane (DCM) was clear, however following the addition of DMDO, drying and reconstitution in 0.1 M sodium bicarbonate (pH 8.1), the solution was an intense yellow colour, in line with previous observations that indicated the presence of the dialdehyde [ 19 ]. To maximize the amount of AFB 1 adducts on the reference material (RM) serum, while ensuring that the adducts formed were similar to those formed in vivo it was necessary to determine the theoretical maximum molar ratio of AFB 1 to HSA.…”
Section: Resultssupporting
confidence: 85%
“…Blank serum (H4522; from human plasma, USA origin, sterile-filtered; Millipore Sigma Burlington, MA, USA), sodium bicarbonate and Oxone ® was purchased from Sigma-Aldrich (Oakville, ON, Canada). Labelled AFB 1 -Lys adduct was prepared according to Renaud et al, (2022) [ 19 ]. In that work, which minimized the production of unwanted reaction by-products, quantitative NMR was used to demonstrate that the previously reported molar attenuation coefficient (ε 400 30,866/M cm) [ 30 ] used for the generation of AFB 1 -Lys standards is valid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in which serum samples were subjected to ambient room and transportation temperatures over timeframes of 4-5 days found that albumin concentrations were stable [17] or increased slightly (2.2%) [18]. It is important to state that the apparent stability of albumin-bound AFB1-lys in serum is not commutable to the storage of free AFB1-lys that would be used as a calibrator, and that stability can vary widely depending on the solvation conditions [19], nor should prolonged storage at room temperature or higher be substituted for the proven robust stability of low temperature (−80 • C) storage [20] when available.…”
Section: Preanalytical Factorsmentioning
confidence: 99%